تطبيق طريقة المحادثة لتحسين مهارة الكلام باللغة العربية لطالبات الصف السابع في مدرسة يسرب (YASRIB) الثانوية للبنات بلاباجونج وطان سوبينج: Penerapan Metode Muhadatsah dalam Meningkatkan Keterampilan Berbicara Dengan Bahasa Arab Santri Kelas 7 MTs Yasrib Putri Watansoppeng - Nopiansyah, Shafiyyah Syawaliah; Munawwir, Ahmad; Al Qifari, Abudzar (Shaut al Arabiyyah, 2025)
This research aims to: 1) determine the Arabic speaking skill before applying the conversation method to improve Arabic speaking skill for seventh-grade female students at YASRIB High School for Girls in Watansoppeng. 2) determine the Arabic speaking skill after applying the conversation method to improve Arabic speaking skill for seventh-grade female students at YASRIB High School for Girls in Watansoppeng. 3) determine the effect of the conversation method before and after its application on improving Arabic speaking skill for seventh-grade female students at YASRIB High School for Girls in Watansoppeng. This research is a quantitative pre-experimental study. The design used is One Group Pretest-Posttest, which is a research design that uses one group without a comparison group. The sample for this research consisted of 15 female students from the tenth grade. The data collection method was testing and documentation, and the research tools were in the form of oral test documentation. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis using the Uji-T test. Based on the results of the analysis using descriptive statistics, it is known that the speaking skill before receiving treatment had an average score of 21.33. The speaking skill after receiving treatment had an average score of 54.33. This means that by using the active knowledge sharing model, there is an increase in learning outcomes of 33.00. Then, based on the results of the inferential statistical analysis using the IBM SPSS version 26 application, a Sig. (2-tailed) score of 0.000 was obtained, which means the significance of the paired sample test is 0.000, indicating that sig is less than 0.05 (0.05 > 0.000), thus accepting the alternative hypothesis (Ha) and rejecting the null hypothesis (Ho). This indicates that there is effectiveness in Arabic speaking skill before and after applying the conversation method to improve Arabic speaking skill for seventh-grade female students at YASRIB High School for Girls in Labuan Bajo and Tan Subing. The implications of this research are: 1) improving speaking skill using the conversation method. 2) This research shows that using various methods can improve learning outcomes. Therefore, it is expected that the teacher will use a varied method.